Midwifery in Health Care System - Siniša Franjić (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
The midwife provides health care for pregnant women and womans in labor and take care for newborn childs and infants. It can also work in gynecological departments by providing basic nursing care to women with reproductive system diseases. The midwife is a health care professional whose field of work is maternity and gynecological health care. It plays an important role in the counseling and education of healthy and ill insured persons and their families.